1990
DOI: 10.1016/0304-3959(90)90055-i
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of a hind limb flexion withdrawal reflex by microinjection of glutamate or morphine into the periaqueductal gray in the rat

Abstract: Microinjection into the midbrain periaqueductal gray (PAG) or lateral reticular formation (LRF) of the neuronal excitant glutamate produces analgesia, and suppresses the responses of a fraction of spinal dorsal horn neurons to noxious heat applied to ventral hind paw skin. Microinjection of morphine into the PAG also produces analgesia, but has been reported to frequently facilitate, as well as to suppress or have no effect, on nociceptive spinal neurons. In anesthetized rats, we tested whether (a) glutamate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Besides the knowledge that PAG is involved in nociceptive transmission, it has been known for several years that electrical stimulation of or opiate microinjections into PAG of animals or humans also produce analgesia (see e.g. 11,17). It has therefore been proposed that in PAG there is some sort of interaction between afferent nociceptive and efferent nociceptive inhibiting transmission (39).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the knowledge that PAG is involved in nociceptive transmission, it has been known for several years that electrical stimulation of or opiate microinjections into PAG of animals or humans also produce analgesia (see e.g. 11,17). It has therefore been proposed that in PAG there is some sort of interaction between afferent nociceptive and efferent nociceptive inhibiting transmission (39).…”
Section: Discussionmentioning
confidence: 99%
“…Descending control originating in the PAG has been shown to powerfully modulate withdrawal reflexes evoked by noxious mechanical and thermal (heat) stimuli (e.g., Mayer et al, 1971;Fardin et al, 1984;Carstens et al, 1990;McMullan and Lumb, 2006a;Leith et al, 2007). However whether this control extends to noxious cold stimulation remains unclear; therefore, the effect of VL-PAG stimulation on cold-evoked withdrawal thresholds and response magnitudes was investigated.…”
Section: Cold-evoked Withdrawal Reflexes Are Significantly Depressed mentioning
confidence: 99%
“…In the PAG and the spinal dorsal horn, the relay centers for pain and sensory information, glycine inhibits glutamate-evoked depolarization and represses the firing of neurons. Also, glutamate seems to be involved in PAG-mediated analgesia: microinjections of glutamate and glutamate agonists into the PAG have been shown to induce analgesia (Carstens et al, 1990). We have previously shown that COX-2 modulated PAG neuronal activity and involved with the regulation of the descending pain control system in the level of PAG neurons.…”
Section: Discussionmentioning
confidence: 97%
“…Several neurotransmitters in the PAG participate in the control of nociception. Among these, endogenous opioids, glycine, and glutamate seem to play a crucial role in the processing of painregulatory signals within this area (Carstens et al, 1990;Renno et al, 1992;Peng et al, 1996;Maione et al, 2000). Glycine is an important inhibitory transmitter in the brainstem and spinal cord.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation